Protection by the Eph–Ephrin System Against Mesenteric Ischemia-Reperfusion Injury. Issue 6 (December 2017) - Vivo, Valentina; Zini, Irene; Cantoni, Anna Maria; Grandi, Andrea; Tognolini, Massimiliano; Castelli, Riccardo; Ballabeni, Vigilio; Bertoni, Simona; Barocelli, Elisabetta
Abstract : ABSTRACT: Mesenteric ischemia-reperfusion (I/R)-induced injury targets primarily endothelial and epithelial cells, leading to a cascade of inflammatory events, eventually culminating in life-threatening syndromes. Hitherto, the role of Eph, the largest family of tyrosine kinase receptors, and of their cell-bound ephrin ligands, whose interaction generates a bidirectional signaling, is still debated in I/R injury. The aim of the present work was therefore to investigate the effects produced by unidirectional activation of forward signaling (administration of chimeric protein ephrinA1-Fc), of reverse signaling (EphA2-Fc), or inhibition of both signals (monomeric EphA2 and the protein-protein interaction inhibitor UniPR1331) on the local and systemic inflammatory responses triggered by mesenteric I/R in mice. When administered at 200 μg/kg i.v., ephrin-A1-Fc prevented intestinal and lung I/R-induced injury, decreasing in the pulmonary district leukocytes recruitment, IL-1β and TNFα levels, and EphA2 overexpression by mesenteric I/R. Blockade of Eph–ephrin signaling by equimolar EphA2 efficiently antagonized I/R-induced gut edema formation, an effect shared also by UniPR1331, mitigated lung mucosal injury, and counteracted the increase in pro-inflammatory cytokines levels. EphA2-Fc 180 μg/kg or equimolar Fc alone did not significantly modify the inflammatory responses to I/R. Our data suggest that the Eph–ephrin system is directly involved in the development of the acute inflammatory process activated in the gut by hypoxia-reoxygenation and in its amplification to distant organs, revealing that a fine pharmacological tuning of this signaling pathway may represent an attractive strategy to contain the I/R-induced inflammatory cascade.